The Missing Parent Compound [(C5H5)Fe(η5‐P5)]: Synthesis, Characterization, Coordination Behavior and Encapsulation. Issue 27 (11th March 2021) - Heinl, Claudia; Peresypkina, Eugenia; Balázs, Gábor; Mädl, Eric; Virovets, Alexander V.; Scheer, Manfred
Abstract: The so far missing parent compound of the large family of pentaphosphaferrocenes [CpFe(η 5 ‐P5 )] (1 b ) was synthesized by the thermolysis of [CpFe(CO)2 ]2 with P4 using the very high‐boiling solvent diisopropylbenzene. It was comprehensively characterized by, inter alia, NMR spectroscopy, single crystal X‐ray structure analysis, cyclic voltammetry and DFT computations. Moreover, its coordination behavior towards Cu I halides was explored, revealing the unprecedented 2D polymeric networks [{CpFe(η 5:1:1:1:1 ‐P5 )}Cu2 (μ‐X)2 ] n (2 a : X=Cl, 2 b : X=Br) and [{CpFe(η 5:1:1 ‐P5 )}Cu(μ‐I)] n (3 ) and even the first cyclo ‐P5 ‐containing 3D coordination polymer [{CpFe(η 5:1:1 ‐P5 )}Cu(μ‐I)] n (4 ). The sandwich complex 1 b can also be incorporated in nano‐sized supramolecules based on [Cp*Fe(η 5 ‐P5 )] (1 a ) and CuX (X=Cl, Br, I): [CpFe(η 5 ‐P5 )]@[{Cp*Fe(η 5 ‐P5 )}12 (CuX)20‐ n ] (5 a : X=Cl, n =2.4; 5 b : X=Br, n =2.4; 5 c : X=I, n =0.95). Thereby, the formation of the CuI‐containing fullerene‐like sphere 5 c is found for the first time. Abstract : After more than 25 years, the synthesis and characterization of the parent compound of the pentaphosphaferrocenes were possible. Its use as building block and template in supramolecular chemistry reveals unprecedented results.